Kualitas gonad bulubabi Tripneustis gratilla dengan pakan rumput laut yang berbeda - Agnette Tjendanawangi; Nicodemus Dahoklory (Jurnal Akuakultur Indonesia, 2019)
ABSTRACT Gonad quality of sea urchin Tripneustis gratilla is influenced by consumed seaweed type. Therefore, this study was conducted to determine the type of seaweed as potential source of carotenoids and produce a good quality of sea urchin gonad. The study was conducted in two phases, namely first phase was to obtain the content of carotenoids and β-carotene from several species of seaweed; and second phase was to testify the seaweed that produced high quality of sea urchin gonad.This study used completely randomized design with 4 treatmens of macroalgae diets, namely: 1. Enhalus sp., 2. Sargassum sp., 3. Ulva sp., and 4. Eucheuma sp. Each treament was repeated three times. Measured parameters were gonad weight, gonad maturity index, gonad color quality, and gonad texture. The study result showed that Enhalus contained the highest carotenoid and β-carotene content with 1409.53 and 639.37 mg/kg respectively. The highest gonad weight was 2.8 g; gonad color and texture was good (score 3); and the highest gonad maturity index was 5.4% that obtained from sea urchin fed with Enhalus. Therefore, this study concludes that Enhalus is potential source of carotenoids for sea urchin T. gratilla diet that will produce a good quality of gonad. Keywords: carotenoid, diet, gonad quality, sea urchin, seaweed.